Bright Kids Tuition Centre Management Information System - Chai, Wei Chun; A. Mostafa, Salama (Applied Information Technology And Computer Science, 2021)
Many tuition centers or franchises still implement the manual record management system to store the personal records of their students and staffs, past examination papers, or any paper documents in their business environments. Record management, storage, and sharing issues have always been closely associated with the manual record management system that is heavily dependent on the file and paper form. This research aims to study the existing processes in Bright Kids tuition centers, design business logics and procedures for the proposed system using the structural approach and develop a web-based system that can resolve these issues. The branch manager, staff, tutor, student, parent, guardian, and guest will be the users of this system. The systems development life cycle (SDLC) model is used as the default software methodology in this project. Through this system, the upper management of Bright Kids can store and manage the employee, student, and guardian records that are shared amongst branches while the students and guardians can view the lecture participated by the students. The past students, staff, or guardians can apply for job applications electronically without visiting the branch. The functionalities or system modules will be unit-tested immediately after they are developed, and they will be integrated-tested after two or more linked modules are completely developed. The functionalities and features are evaluated in the testing phase via the construction and implementation of test cases. The results of test cases and user acceptance testing will be documented in this report. At the end of this report, the advantages, limitations, and recommendations of the developed system will be discussed in the conclusion section.